2020
DOI: 10.3390/md18010041
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diversity in Species Belonging to Soft Coral Genus Sacrophyton and Its Impact on Biological Activity: A Review

Abstract: One of the most widely distributed soft coral species, found especially in shallow waters of the Indo-Pacific region, Red Sea, Mediterranean Sea, and also the Arctic, is genus Sacrophyton. The total number of species belonging to it was estimated to be 40. Sarcophyton species are considered to be a reservoir of bioactive natural metabolites. Secondary metabolites isolated from members belonging to this genus show great chemical diversity. They are rich in terpenoids, in particular, cembranoids diterpenes, tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 124 publications
0
63
0
Order By: Relevance
“…As the marine environment is an important source of bioactive substances, and due to the high chemical diversity and specimen diversity of the Sarcophyton genus [27,28,34,35], it can be expected that new natural products and activities from soft corals of this genus can be continuously discovered in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As the marine environment is an important source of bioactive substances, and due to the high chemical diversity and specimen diversity of the Sarcophyton genus [27,28,34,35], it can be expected that new natural products and activities from soft corals of this genus can be continuously discovered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…All compounds were found to possess anti-inflammatory activity by exhibiting inhibitory effects on the generation of superoxide anion and elastase release in fMLF/CB-induced primary human neutrophils, and cherbonolides G and H ( 2 and 3 ) were found to be the most active in the inhibition of elastase release and superoxide anion generation, respectively. As the marine environment is an important source of bioactive substances, and due to the high chemical diversity and specimen diversity of the Sarcophyton genus [ 27 , 28 , 34 , 35 ], it can be expected that new natural products and activities from soft corals of this genus can be continuously discovered in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that species of Sarcophyton are rich sources of compounds, such as cembranoids [ 13 , 14 , 15 , 16 ], biscembranoids [ 17 , 18 , 19 , 20 , 21 ], and steroids [ 22 ]. Until now, more than 500 marine natural objects have been found from the soft corals of the genus Sarcophyton [ 23 ]. It is worth mentioning that biscembranoid-type metabolites are mainly biosynthetically rationalized by a Diels–Alder reaction of two monocembranoidal members, a 1,3-diene cembranoid unit, and a dienophile cembranoid unit.…”
Section: Introductionmentioning
confidence: 99%